2014
DOI: 10.1175/jas-d-13-0153.1
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multiscale Intensity Metric for Evaluation of Tropical Cyclone Intensity Forecasts

Abstract: In this study, a new multiscale intensity (MSI) metric for evaluating tropical cyclone (TC) intensity forecasts is presented. The metric consists of the resolvable and observable, low-wavenumber intensity represented by the sum of amplitudes of azimuthal wavenumbers 0 and 1 for wind speed within the TC vortex at the radius of maximum wind and a stochastic residual, all determined at 10-m elevation. The residual wind speed is defined as the difference between an estimate of maximum speed and the low-wavenumber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 24 publications
(36 reference statements)
3
27
0
Order By: Relevance
“…Forecast errors remain about constant through 108 h and increase by 120 h, probably due to the small sample size (Fig. The runs with no data assimilated have a substantial high intensity bias after 36 h. The low intensity biases in the short range for all three sets of runs may be due to the vortex spindown issue discussed in Vukicevic et al (2013), and suggest that this issue is also important in the vortex initialization scheme. The difference between the forecast intensity errors is expected to be larger than for track errors, since intensity is at least partially controlled by processes within the TC core.…”
Section: ) Standard Verificationmentioning
confidence: 92%
See 1 more Smart Citation
“…Forecast errors remain about constant through 108 h and increase by 120 h, probably due to the small sample size (Fig. The runs with no data assimilated have a substantial high intensity bias after 36 h. The low intensity biases in the short range for all three sets of runs may be due to the vortex spindown issue discussed in Vukicevic et al (2013), and suggest that this issue is also important in the vortex initialization scheme. The difference between the forecast intensity errors is expected to be larger than for track errors, since intensity is at least partially controlled by processes within the TC core.…”
Section: ) Standard Verificationmentioning
confidence: 92%
“…Aksoy et al (2013) demonstrated the value of assimilating airborne Doppler radar radial wind data with HEDAS on 83 cases in 20 TCs during the 2008-11 seasons. Vukicevic et al (2013) found that these errors were caused by a short-term spindown of the entire vortex circulation in each data assimilation cycle, and that the magnitude was correlated with the TC intensity. They showed direct positive impact on the vortex wind structure, but also indirect positive impact on the thermodynamic structure.…”
Section: Introductionmentioning
confidence: 96%
“…One remaining question is can these analyses be used in some predictive or verification capacity? Vukicevic et al (2014) compared the low wavenumber maximum from a TC model against those determined from SFMR data and proposed their use as an alternative method of forecast verification. A next step here is to reproduce a similar comparison but with the scatterometer data.…”
Section: Discussionmentioning
confidence: 99%
“…To determine and quantify motion and shear-dependent low wavenumber asymmetric surface wind structure using global scatterometer data, the present study expands on previous work from Vukicevic et al [(2014), herein referred to as V14] and U14 that examined surface wind asymmetry from SFMR and model data. In V14, a…”
Section: Low Wavenumber Analysismentioning
confidence: 98%
See 1 more Smart Citation